Effect of Planned Early Ambulation on Psychophysical Well-being of Post-cesarean Patients - Rajesh Thakur, Jyoti (International Journal of Nursing Research, 2023)
Introduction: As the well-being of maternal and child health occupies paramount place in health-care delivery system, cesarean section (CS) has become the most common intervention in obstetrics discipline. Since the past 25 years, factors such as medical, psychological, social, financial, and legal seem to have contributed to rise in CS rates. In spite of changes in its indications, CS is currently performed to benefit the fetus, not the mother. The present study aimed to study the effect of planned early ambulation on post-cesarean patients. Materials and Methods: Quasi-experimental approach with preand post-intervention multiple time series study design was adopted. A non-probability purposive sampling technique was used to meet sample size of 500, distributed equally in experimental and control groups. With routine post-cesarean care, planned early ambulation was initiated for the experimental group on the day of LSCS and was followed twice a day for the first 5 post-cesarean days. The study subjects of control group were refrained from this intervention. At the end of each day, the desired data were collected by structured observation and self-report techniques. Results: The study subjects of the experimental group had better responses in relation to selected aspect of psychophysical well-being as compared to the control group. The significant difference was noted in the selected aspects of psychophysical well-being among the experimental and control groups. Conclusion: The study concluded that planned early ambulation is effective strategy in achieving early psychophysical well-being in post-cesarean patients.